DISASTER, MENTAL HEALTH AND RESCUING MEDICAL PROFESSIONALS - GADIT, AMIN A. (Journal of Ayub Medical College Abbottabad, 2005)
The human beings have a certain threshold to cope with the adverse life events which depends on the strength of coping abilities which are a part of personality make-up and augmented by effects of environment, type of up bringing and related social circumstances to which exposure has occurred during the various stages of life cycle. The neurochemistry does have an important part to play and of special mention is the stress related hormones, which play an effective role in helping the individual to withstand the jolts of life. The more one is exposed to adversities the better sensitization leading to relative indifference is acquired that leads to some psychological strength which can help in maintaining emotional equilibrium in times of severe stress. Human beings build new learned behavior on top of bio-genetically predetermined templates. Brain plasticity makes humans extremely sensitive to environment which can have major health-related pathogenic effects. Most adverse mental health consequences of disasters may, therefore, be attributed to our immense ability to learn, remember, and re-shape behavior on the basis of new-including catastrophic-experiences. Medical doctors fall under the category of those who deal with illnesses, casualties and emergencies. During the process of training and until assuming the full role as medical practitioners they would have developed adequate psychological strength, which helps in addressing the problems of the patients. However, there are circumstances where there is an encounter with natural disasters which is characterized by severe disruption in ecological and psychological systems exceeding the coping capacity of the individuals and communities,1 this can be nerve wrecking and may have serious effects on the psyche of even the rescuers. Recent disaster in Pakistan, came unexpected and brought in heavy magnitude of destruction which affected the people both physically and psychologically while causing a tremendous amount of fear and uncertainty among those who were not directly affected by this disaster. Print media reported the contributions made by mental health professionals and others in helping the victims coming to terms with the consequences of the disaster but the important issue which needs attention here is about the direct care givers, many of whom were affectees and at the same time were required to attend to the medical needs of thousands and thousands of victims. As an individual, the doctors also fall in the parameter of other human beings when it comes to their personality make up, psychological strength, personal sensitivities and previous personal social and psychological issues. The issue of secondary traumatic stress which currently is not recognized as a clinical disorder2 may produce symptoms among medical rescuers like: hyper arousal, intrusive symptoms, emotional numbing, anxiety and depression along with compassion stress which includes helplessness, confusion, isolation, secondary traumatic stress symptoms ultimately leading to a state of exhaustion and dysfunction.3 There is also a possibility of developing vicarious traumatization which is a feature developing in therapeutic workers helping trauma survivors affecting: relationship with meaning and hope, intelligence, will power, sense of humor, ability to protect oneself, memory, sense of connection to others, self tolerance, cognitive reactions, and cause physical symptoms like: tension, fatigue, edginess, difficulty sleeping, bodily aches, change in biological needs, etc, which are associated with behavioral changes like: becoming judgmental of others, becoming cynical or angry, becoming over involved, developing rigid boundaries, heightened protectiveness, avoiding social and work contacts. Studies4, 5 have shown the incidence of PTSD (post traumatic stress disorder) among the rescuers upto the magnitude of 14%, the other serious outcome is in the form of depression which is noted to be about 40%, acute stress disorder develops mostly among young and single, 16% of the rescuers may develop anxiety disorder and substance abuse. It is worth noting that risk for PTSD is four times than the general population.6 Reports indicated that in the current circumstances doctors are also vulnerable to depression in the background of 6% prevalence of clinical depression in Pakistan.7 There is also a risk of precipitation of psychosis subject to genetic vulnerability. There is evidence that the immune system gets compromised and open avenues for many physical illnesses to manifest apart from the social decompensation.8 However, in minority of cases the rescuing physician may emerge as a changed person with positive attributions to personality acquiring great emotional strength, becoming more humane and the transformation into a refined person. It is utmost important to address the mental health issues among the general doctors who are involved in rescue efforts and therapeutic relationship. Who should help? The mental health professionals who are trained in emergency J Ayub Med Coll Abbottabad 2005; 17(4) psychiatry can be of help but we have to keep in mind the extreme dearth of psychiatrists, lack of training in crises psychiatry and the fact that all the mental health professionals cannot and should not get involved as it is important to address the personal sensitivities and fitness apart from having adequate insight into the different psychotherapeutic issues. The role of religious workers appreciating the importance of spiritual model of treatment and help from allied mental health professionals is also important. Camp type services result in futility; hence long-term follow up is desirable. It is also essential that the mental health professional is well versed with CISD and EMDR techniques and has insight into the role of pharmacological interventions in such situations. Critical incident stress debriefing (CISD)9 is a brief, structured, intervention technique used immediately or shortly after traumatic event that attempts to assist participants in a group setting in cognitively and emotionally processing their experience. CISD is now a part of a comprehensive spectrum of techniques called critical incident stress management (CISM) which promote emotional health through verbal expression, cathartic ventilation, normalization of reactions, health education and preparation for possible future reactions.EMDR (eye movement desensitization reprocessing)10 can be an effective part of de-briefing session. The physicians response to mass casualty must address the high volume of patients with anxiety reactions and somatic symptoms likely to present for care, supportive interventions include fostering a sense of safety and efficacy, connecting patients with communities and services, and helping patient talk about the trauma, in the future, early pharmacological interventions may prove to be effective. At site, it is useful for the rescue doctors to develop self therapeutic strategies in order to build psychological strength and prevent mental stress and its associated complications for example: developing buddy system with co-doctor, mutual encouragement and support, frequent time out, staying in touch with family and friends, ventilation of emotions and feelings, physical exercise, yoga, meditation, adequate nutrition and remaining in groups whenever possible. The American Psychiatric Association (APA) has formed a committee on psychiatric dimensions of disasters and has produced guidelines, which is an important reading especially for mental health professionals.11 Pakistan has suffered for a long time the consequences of terrorism and man initiated disasters, which have caused significant mental health morbidity, and the current calamity has added much more for the enduring capacity of the nation as a whole. As it is vitally important to address the issues related to mental health of the medical practitioners dealing with the rescue work and treatment, the government should devise strategies, which can look into this matter in a beneficial way in order to prevent the mental health morbidity among the healers. The medical practitioners at their end are required to be equipped well for the disasters in terms of further strength building and coping emotionally with mass casualties and hence have to liaise with organizations dealing with the issues in disaster preparedness and training and to acquire adequate insight into the bio-psycho-socio-spiritual models of both treatment as well as prevention.